2022
DOI: 10.1177/13634615221105114
|View full text |Cite
|
Sign up to set email alerts
|

The culturally and contextually sensitive assessment of mental health using a structured diagnostic interview (MINI Kid) for Syrian refugee children and adolescents in Lebanon: Challenges and solutions

Abstract: Elevated rates of mental health difficulties are frequently reported in conflict-affected and displaced populations. Even with advances in improving the validity and reliability of measures, our knowledge of the performance of assessment tools is often limited by a lack of contextualization to specific populations and socio-political settings. This reflective article aimed to review challenges and share lessons learned from the process of administering and supervising a structured clinical interview. We admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…It has been shown to be valid and reliable in clinical and population-based samples of adolescents. [23][24][25][26] Responses are binary (no/yes), and screening questions are used for each illness module on the MINI-KID. If the screening questions are not endorsed, the module is skipped.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown to be valid and reliable in clinical and population-based samples of adolescents. [23][24][25][26] Responses are binary (no/yes), and screening questions are used for each illness module on the MINI-KID. If the screening questions are not endorsed, the module is skipped.…”
Section: Methodsmentioning
confidence: 99%
“…Intercultural work challenges this assumption by raising questions about the cross-cultural applicability of standard instruments. Kyrillos et al (2023) drew data from a larger study of Syrian refugee children and adolescents in Lebanon to consider how the MINI International Neuropsychiatric Interview for Children and Adolescents (MINI Kid; Sheehan et al, 2010) functioned in clinical assessments. They found that attention paid to cultural norms and meanings during the assessments was critical to accurately interpreting results.…”
Section: The Need For Culturally Adapted Mental Health Servicesmentioning
confidence: 99%